Poly(vinyl chloride)/nanoclay nanocomposites - electrical and mechanical properties - Dimitry, O. I.; Sayed, W. M.; Mazroua, A. M.; Saad, A. L. (Polimery, 2009)
Poly (vinyl chloride) (PVC) and dioctyl phthalate (DOP) plasticizer were mixed with small amounts (1-10phr) of a layered silicate nanoclay consisting of 83.3% of montmorillonite and 16.7% of kaolinite to obtain PVC-based nanocomposites. The thermalstability of obtained products was characterized by thermal analysis using a thermogravimetric analyzer (TGA). The electrical conductivity of these composites was studied as a function of temperature and it was found that the activation energy for this property is lower than that of the host polymer. The composites exhibit increased Young’s modulus and decreased Shore A hardness.